A new scanning lines distribution strategy for the form error evaluation of freeform surface on CMM. (August 2021) - Sang, Yicun; Yan, Yichen; Yao, Chenglin; He, Gaiyun
Highlights: The proposed strategy aims to improve scanning quality for the form error inspection. The relative value of the probability to generate larger form error is describe in a model. A star-shaped mode is introduced to generate initial scanning lines. A method is proposed to adaptively allocate scanning lines number according to model. Two criteria are set to delete redundant scanning lines according to the given number. Abstract: Form error evaluation is a vital and indispensable means of evaluating the machining quality of freeform surfaces. Scanning on coordinate measuring machines (CMMs) is increasingly used in the inspections of freeform surfaces. This work aims to improve the inspection accuracy and efficiency of scanning for the form error evaluation of freeform surfaces determined by the scanning lines distribution strategy. A new scanning line distribution strategy is proposed to adaptively distribute the scanning lines using star-shaped mode. Experiments and simulations are performed to test the accuracy and efficiency of the proposed strategy through comparison with existing scanning strategies.